2009
DOI: 10.4049/jimmunol.182.1.309
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to MHC Class I Induce Autoimmunity: Role in the Pathogenesis of Chronic Rejection

Abstract: Alloimmunity to mismatched donor HLA-Ags and autoimmunity to self-Ags have been hypothesized to play an important role in immunopathogenesis of chronic rejection of transplanted organs. However, it is not known what role, if any, alloimmune response plays in inducing autoimmunity. To test whether Ab-developed posttransplantation to mismatched donor MHC induces autoimmunity and chronic rejection, we developed a murine model wherein anti-MHC class I Abs or control (C1.18.4/anti-keratin) were administered intrabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
226
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 145 publications
(235 citation statements)
references
References 55 publications
8
226
0
1
Order By: Relevance
“…VITTAL et al [10] reported that col(V) was highly overexpressed in the IPF lung. In addition, pre-clinical studies have confirmed that anti-col(V) autoimmunity can result in fibrotic changes in the lung [11,14].…”
Section: Introductionmentioning
confidence: 94%
“…VITTAL et al [10] reported that col(V) was highly overexpressed in the IPF lung. In addition, pre-clinical studies have confirmed that anti-col(V) autoimmunity can result in fibrotic changes in the lung [11,14].…”
Section: Introductionmentioning
confidence: 94%
“…While the mechanisms of AMR are not firmly established, de novo donor-specific antibodies against HLA have been shown to predispose to the development of immune responses to lung self-antigens and BOS (69)(70)(71). To define mechanisms leading to anti-MHC-mediated development of rejection, a preclinical murine model was developed in which exogenous anti-MHC was administered into the native lungs and elicited production of antibodies and T cell responses specific for lung-associated self-antigens, type V collagen [col(V)], and K-α 1 tubulin, culminating in fibrotic pathology (72,73). Human lung transplant recipients develop antibodies against col(V), a protein mainly located in the lung interstitium and not ordinarily exposed to the immune system.…”
Section: Armentioning
confidence: 99%
“…It is accepted that blood group antigens and HLA class I and II are not targets for AECA-associated autoimmune disease. 15 The AECAs may be joined to destructive potential of PRA on graft endothelial cells.…”
Section: Discussionmentioning
confidence: 99%